Long noncoding RNA THRIL promotes foam cell formation and inflammation in macrophages. (13th October 2022) - Song, Xiaosu; Gao, Fen; Li, Hong; Qin, Weiwei; Chai, Chanjuan; Shi, Guojuan; Yang, Huiyu
Abstract: Tumor necrosis factor‐α (TNF‐α) and heterogenous nuclear ribonucleoprotein L (hnRNPL)‐related immunoregulatory lincRNA (THRIL) is a long noncoding RNA (lncRNA) involved in various inflammatory diseases. However, its role in atherosclerosis is not known. In this study, we aimed to investigate the function of THRIL in mediating macrophage inflammation and foam cell formation. The expression of THRIL was quantified in THP‐1 macrophages after treatment with oxidized low‐density lipoprotein (oxLDL). The effect of THRIL overexpression and knockdown on oxLDL‐induced inflammatory responses and lipid accumulation was determined. THRIL‐associated protein partners were identified by RNA pull‐down and RNA immunoprecipitation assays. We show that THRIL is upregulated in macrophages after oxLDL treatment. Knockdown of THRIL blocks oxLDL‐induced expression of interleukin‐1β (IL‐1β), IL‐6, and TNF‐α and lipid accumulation. Conversely, ectopic expression of THRIL enhances inflammatory gene expression and lipid deposition in oxLDL‐treated macrophages. Moreover, THRIL depletion increases cholesterol efflux from macrophages and the expression of ATP‐binding cassette transporter (ABC) A1 and ABCG1. FOXO1 is identified as a protein partner of THRIL and promotes macrophage inflammation and lipid accumulation. Furthermore, overexpression of FOXO1 restores lipid accumulation and inflammatory cytokine production in THRIL‐depleted macrophages. In conclusion, our data suggest a model where THRIL interacts with FOXO1 to promote macrophage inflammation and foam cell formation. THRIL may represent a therapeutic target for atherosclerosis.